[OP.4A.04] NON-INVASIVE HEMODYNAMIC MONITORING AS A GUIDE TO DRUG TREATMENT OF UNCONTROLLED HYPERTENSIVE PATIENTS: HOME BLOOD PRESSURE IN THE BEAUTY STUDY. (September 2017) - Talvik, A.; Rebora, P.; Salerno, S.; Miszkowska-nagórna, E.; Liu, X.; Heinpalu-kuum, M.; Comotti, T.; Swierblewska, E.; Valsecchi, M.G.; Kjeldsen, S.E.; Viigimaa, M.; Narkiewicz, K.; et al.
Abstract : Objective: In the BEAUTY study we investigated whether utilizing non-invasive monitoring of hemodynamic parameters combined with a drug selection algorithm (integrated hemodynamic management-IHM) compared to conventional drug selection may improve uncontrolled hypertension. Design and method: Uncontrolled (office systolic blood pressure (SBP)>140 mmHg and ambulatory daytime SBP>135 mmHg while taking >2 antihypertensive drugs) essential hypertensive patients were referred to 5 European Hypertension Excellence Centers and were randomized to IHM-guided (n = 83) vs. conventional (control, n = 84) treatment adjustment in an investigator-initiated multicentre prospective randomized parallel groups controlled study. The average number of antihypertensive drugs increased from 3.1 to 4.1 in both groups and differed only in a rise of the use of diuretics in the IHM groups (from 13 to 31%). Results: Home SBP was available in 46 IHM and 38 controls displayed at 6 months significantly greater reduction in IHM (−21.1 ± 17.7 mmHg) than in controls (−10.2 ± 13.0 mmHg, P = 0.002). Home SBP changed from 152.1 ± 15.8 and 149.8 ± 11.8 mmHg to 131.0 ± 11.1 and 139.6 ± 12.8 mmHg in IHM group and Control group, respectively, showing significantly greater reduction in IHM than in Control group (p = 0.002), which remained significant after multiplicity adjustment and after adjusting for baseline home SBP, recruiting center, age, sex and BMI (p < 0.0001). Figure. No caption available. Conclusions: Non-invasive hemodynamic monitoring associated with a drug selection algorithm induced larger reduction in home BP compared to conventional drug selection in uncontrolled hypertensive patients referred to European Hypertension Excellence Centers. Thus, these home BP taken by patients themselves may suggest that the integrated hemodynamic monitoring after all maybe useful in at least subgroups of the patients with uncontrolled hypertension.